Multimicronutrient Slow-Release Fertilizer of Zinc, Iron, Manganese, and Copper - Siladitya Bandyopadhyay; Kunal Ghosh; Chandrika Varadachari (International Journal of Chemical Engineering)
The process for the production of a slow-release micronutrient fertilizer is described. The compound contains zinc, iron, manganese, and copper as micronutrients and is produced by polymerizing a system containing phosphoric acid, zinc oxide, hematite, pyrolusite, copper sulfate, and magnesium oxide followed by neutralization of the polyphosphate chain with ammonium hydroxide. Changes in temperature, density, and viscosity of the reaction system during polymerization were studied. Reaction kinetics was studied at three different temperatures. Rate curves revealed a multistage process with essentially linear rates at each stage. Thus, each stage displayed zero order kinetics. The product was crystalline and revealed ordering of P-O-P chains. It had low solubility in water but high solubility in 0.33 M citric acid and 0.005 M DTPA. Three different field trials showed significant yield increments using the slow-release micronutrient fertilizer compared to the conventional micronutrients. Yield increments in rice were in the range of 10–55% over control (with no micronutrient) and up to 17% over the conventional micronutrient fertilizers. There were significant increases in total uptake of zinc, iron, and manganese in the grain. Slow-release fertilizers also produced significant yield increases in potato as well as significant increase in vitamin C content of the tuber.